ความพึงพอใจของผู้เดินทางด้วยรถโดยสารประจำทาง และการยอมรับของผู้เดินทาง ต่อระบบขนส่งสาธารณะแบบก้าวหน้าในกรุงเทพมหานคร - ชรัด พิริยะวัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The thesis examined the customer satisfaction on quality of bus services and determined the service choice of the improvement with the introduction of two Advanced Public Transportation Systems (APTS) components; Automated Fare Payment (AFP) and Automated Traveler Information Systems (ATIS). Data on riders’ perception and preference were collected by interview survey from the target group (bus passengers). The interview was targeted on two traveling purposes, commuter (work) and shopping. The interviewees’ attitude towards the service on various factors was sought by mean of gap score as indicated in TCRP Report 47 while the service choice selection of passengers employed stated preference technique. The customer satisfaction on various travel factors was analyzed by Impact Score Techniques and Quadrant Analysis. The user acceptance on the service improvement was measured by stated preference technique and the service choice model was then developed in the form of Binary Logit Model. The results of the study indicated that the factors reported defective by riders considering from the travel for shopping purpose were comfort, the update of bus and devices, travel time, and cleanness, whereas comfort, the behavior of driver, the availability of seats, and convenience were stated in the purpose of traveling for work. The conclusion showed that the majority of passengers (60%) was interested in improving the service by the introduction of APTS in both trip purposes. For shopping trips, bus riders preferred the AFP to ATIS while commuting passengers put more importance on ATIS.